Pengaruh Pelayanan Dan Kualitas Produk Terhadap Keputusan Pembelian Air Galon Isi Ulang Pada Depot Air Qua Di Tegal Alur Jakarta Barat - Wahyu Pamungkas Putro; Budi Santosa Kramadibrata (International Forum of Researchers and Lecturers, 2024)
Clean water is a crucial element in the lives of humans and other creatures, ensuring the normal function of the body's organs and optimal health. In the bottled water industry, particularly in refillable bottled water, competition is becoming increasingly fierce. This study focuses on the role of service and product quality in consumer purchasing decisions at Refillable Bottled Water Depots, specifically at Depot Air Qua in Tegal Alur, West Jakarta. The research employs an associative quantitative approach with 96 respondents and questionnaires as instruments. The analysis results indicate a positive impact between service and product quality on purchasing decisions. It is essential to note that this analysis is limited to a single Refillable Bottled Water company (Depot Air Qua) without considering other variables or moderating factors that could affect purchasing decisions more comprehensively.